Pelayanan Pastoral Terhadap Pertumbuhan Gereja Kemah Injil Kingmi Papua Jemaat Smirna Di Kota Sorong - Heni Sigap; Yulian Anouw; Jean Anthoni (Departement of Mathematics Education, 2023)
A growing church is not measured by the extent of the number of churches built, or (the quantity of construction) and the church is not a building even though the church is a place of fellowship and service, but rather the growth of the church. measured by how effectively the service is carried out. This research was conducted to see the growth of the church in the form of services at the Kingmi Papua Gospel Tent Church, Smyrna Congregation in Sorong. Based on the data that the author has studied, it turns out that the role of pastoral care is very significant in church growth. Based on the background above, research was carried out on the Smyrna congregation at the Kingmi Gospel Tabernacle Church, Papua Sorong, to examine several things, first, the leader or pastor. Second, to the congregation and third, background, service time. Thus, pastoral care aims to help and guide the congregation in behaving, preventing or overcoming the problems they face independently and responsibly. So that pastoral ministry has good goals and functions